Does Vitamin D Prophylaxis in Pregnancy Decrease the Risk of Adverse Neonatal Outcomes? [33N]. (May 2018) - Persad, Malini D.; Ly, Victoria; Herrera, Kimberly; Demishev, Michael; Quirk, J. Gerald; Garretto, Diana
Abstract : INTRODUCTION: Maternal vitamin D deficiency has been associated with adverse neonatal outcomes including preterm birth, immunosuppression, infection, low birth weight, neonatal seizures, asthma and fractures. We set out to determine if antepartum vitamin D prophylaxis decreases the risk of adverse neonatal outcomes. METHODS: A prospective cohort study was performed at a university hospital between October 2016 to July 2017. Included in the study were women with a confirmed intrauterine pregnancy, between 12-16 weeks gestation. Excluded from the study were women taking vitamin D supplements prior to enrollment, diagnosed with a malabsorption disorder, or carrying a fetus with a known anomaly. Women were assigned to receive vitamin D 3000IU daily or no supplement in addition to prenatal vitamins. Participants were routinely assessed for medication compliance. Neonatal factors were collected and compared between those who were compliant and those who were not. Adverse neonatal events were defined as preterm birth, Apgar score < 5 and 7 at 1 and 5 minutes respectively, NICU admission, or fetal death. Parametric and nonparametric statistics were used to compare groups. RESULTS: 72 women were included in the study. There was no statistically significant difference in demographic characteristics between groups. Women receiving vitamin D delivered at a statistically significant greater gestational age, with no deliveries occurring prior to 34 weeks gestation. There was no difference in adverse neonatal events. CONCLUSION: Vitamin D prophylaxis in pregnancy may decrease the risk of preterm birth.